La recepció d'Ausiàs March al segle XVI: l'edició de Romaní (1539) - López Casas, Maria Mercè (Caplletra. Revista Internacional de Filologia, 2003)
Complete and detailed description of all the currently known copies of the edition of Ausiàs March’s poetry published by Baltasar de Romaní (València 1539). The author considers as stimulating the hypothesis explaining the edition as aninitiative by Ferdinand of Aragon to introduce March and his verse into Castilian Spanish, which would explain why Romaní made a selection of text in Catalan with the corresponding Spanish translation.